2012
DOI: 10.1186/1749-7922-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of total white blood cells and neutrophil counts in patients with suspected appendicitis: retrospective study

Abstract: IntroductionAcute appendicitis (AA) is common surgical problem associated with acute-phase reaction. Blood tests role in decision-making process is unclear. This retrospective study aimed to determine diagnostic value of preoperative evaluation of white blood cells (WBCs) and neutrophils and its value in predicting AA severity.MethodsMedical records of 456 patients who underwent appendectomy during 4-years period were retrospectively reviewed. Patients were subdivided according to histological finding into: no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 25 publications
3
34
0
1
Order By: Relevance
“… 11 , 12 In several published studies, the sensitivity and specificity of LC in the diagnosis of AA has been reported as 67%-97.8% and 31.9%-80%, respectively. 13 , 14 The present study found that LC was significantly higher in AA, and the sensitivity and specificity of LC were 94% and 75%, respectively.…”
Section: Discussionsupporting
confidence: 45%
“… 11 , 12 In several published studies, the sensitivity and specificity of LC in the diagnosis of AA has been reported as 67%-97.8% and 31.9%-80%, respectively. 13 , 14 The present study found that LC was significantly higher in AA, and the sensitivity and specificity of LC were 94% and 75%, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…Studies done in the United States, California University, NA rate was (9%). In Saudi Arabia, Arar central hospital NA rate was (3%), and In Jeddah KAUH 2012 NAR was (6.4%) ( 17 - 19 ). A study was done in Riyadh, in the period 1998-2003 found those 23±8.67 years is the mean age-associated more with NA ( 20 ).…”
Section: Discussionmentioning
confidence: 97%
“…Al-Gaithy et al [12] have studied four hundred and fifty-six patients with appendicitis while trying to determine the diagnostic value of leucocyte count and neutrophil ratio and the relation of these inflammatory markers with the severity of acute appendicitis. They have stated that leukocyte and neutrophil counts cannot be used as single diagnostic tests for acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%